Effectiveness of Combined Strategies for the Prevention of Hypothermia Measured by Noninvasive Zero-Heat Flux Thermometer During Cesarean Section - Cotoia, Antonella; Mariotti, Paola Sara; Ferialdi, Claudia; Del Vecchio, Pasquale; Beck, Renata; Zaami, Simona; Cinnella, Gilda (Frontiers in Medicine, 2021)
Background: perioperative hypothermia (body temperature <36°C) is a common complication of anesthesia increasing risk for maternal cardiovascular events, coagulation disorders and it can also influence neonatal health. The aim of our study was to evaluate the impact of combined strategies of warming on maternal core temperature, measured with the SpotOn. We hypothesized that combined modality of active warming prevents hypothermia in pregnant women undergoing caesarean delivery with spinal anesthesia. Methods: 78 pregnant women were randomly allocated into three study groups receiving warmed IV fluids and forced-air warming (AW), warmed IV fluids (WF), no warming (NW). Non-invasive core temperature device (SpotOn) measured maternal core temperature intraoperatively and for 30 minutes after surgery. Maternal mean arterial pressure, incidence of shivering, thermal comfort and newborn’s APGAR, axillary temperature, weight and blood gas analysis were also recorded. Results: incidence of hypothermia was of 0% in AW, 4% in WF and 47% in NW. Core temperature in AW was constantly higher than WF and NW groups. Incidence of shivering in perioperative time was significantly lower AW and WF groups respect to NW (P<0.04). Thermal comfort was higher in both AW and WF groups compared to NW (P=0.02 and P=0.008 respectively). There were no significant differences among groups for the other evaluated parameters. Conclusion: combined modality of active warming is effective in preventing perioperative hypothermia. The routine uses of combined forced-air warming and warmed IV fluids is suggested in the setting of caesarean delivery. Key words: spinal anesthesia; core temperature; perioperative hypothermia; caesarean delivery; SpotOn.